Perceptions of Rambu Solo’ as a Torajan Cultural Identity in the Era of Globalization - Munaing; Roselinda; Hasrini, Sry (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This study aims to explore the perceptions of Torajan youth, particularly members of the PPGT Marante Congregation, toward the traditional Rambu Solo’ ceremony. The research employed a qualitative approach with three respondents selected based on the following criteria: active involvement in PPGT, understanding of Rambu Solo’, willingness to participate as respondents, and Torajan cultural background. Data were collected through in-depth interviews and analyzed thematically, emphasizing three main dimensions: cognitive, affective, and conative. The findings reveal that, cognitively, Rambu Solo’ is perceived as a customary obligation with profound spiritual meaning—not merely a funeral ritual but also a means of honoring ancestors and symbolizing cultural identity. Affectively, the respondents’ emotional attachment is reflected in their motivation to preserve the tradition through solidarity, mutual cooperation, kinship, and church support that strengthens the spiritual aspect. Meanwhile, in the conative dimension, respondents demonstrate determination and orientation to sustain Rambu Solo’ through concrete actions such as integrating customary values with Christian faith, digital documentation, social media utilization, and cultural education among the younger generation. These findings affirm that Torajan youth’s perceptions of Rambu Solo’ are influenced by internal factors—such as cultural identity, personal experience, and preservation commitment—and external factors, including family, church, PPGT community, formal education, digital media, and the challenges of globalization. Thus, Rambu Solo’ is not merely regarded as a traditional ritual but as a symbol of cultural identity that reinforces social solidarity and cultural resilience among the Torajan people in the modern era.